Implementation of Thought K.H. Batshul Birri in the Development of Al-Qur'an Science Education at Darul Hikmah Islamic Boarding School Kyai Abdan - Zaenal Abidin; Ahmad Aghus Ulinuha; Ita Wijayanti (Universitas Ahmad Dahlan, 2023)
Education based on the Qur'an, both in the form of practicing the contents of the Qur'an and learning related to procedures for reading whether it is tajwid or its makhraj, as for one of the books on how to read the Koran which is so well known among pesantren namely books by K. H. Maftuh Batshul Birri Lirboyo Kediri. The aims of this research are: (1) To find out the thoughts of K.H. Maftuh Batshul Birri in developing Al-Qur'an science education. (2) Knowing the implementation of K.H. Maftuh Basthul Birri for the progress of education in the science of the Qur'an at Darul Hikmah Islamic Boarding School Kyai Abdan Pakis Magelang. This study uses a descriptive qualitative approach, which is a study aimed at describing and analyzing phenomena, events, social activities, attitudes, beliefs, perceptions, and thoughts of people individually and in groups. Data sources come from primary and secondary. Data collection through observation, interviews, and documentation. Technical data analysis by reducing data, displaying data and drawing conclusions. This study describes the thoughts of K.H. Maftuh Batshul Birri in the development of Al-Qur'an science education he wrote in several books written by him, namely Jet Fighter, Fathul Manan and Tuhfathul Athfal. The benefit of this research is the progress of education in the science of the Koran at the Darul Hikmah Islamic Boarding School Kyai Abdan Pakis Magelang because it uses the fighter jet, tajwid and room ottoman methods so that most likely what K.H. Maftuh Batshul Birri composed/taught really supports learning the science of the Qur'an at the Kyai Abdan Islamic Boarding School.